Segmental Duplications Flank the Multiple Sclerosis Locus on Chromosome 17q - Chen, Daniel C.; Saarela, Janna; Clark, Royden A.; Miettinen, Timo; Chi, Anthony; Eichler, Evan E.; Peltonen, Leena; Palotie, Aarno (Genome Research, 2004)
Large chromosomal rearrangements, duplications, and inversions are relatively common in mammalian genomes. Here we report interesting features of DNA strands flanking a Multiple Sclerosis (MS) susceptibility locus on Chromosome 17q24. During the positional cloning process of this 3-Mb locus, several markers showed a radiation hybrid clone retention rate above the average (1.8-fold), suggestive for the existence of duplicated sequences in this region. FISH studies demonstrated multiple signals with three of the tested regional BACs, and 24 BACs out of 187 showed evidence for duplication in shotgun sequence comparisons of the 17q22–q24 region. Specifically, the MS haplotype region proved to be flanked by palindromic sequence stretches and by long segmental intrachromosomal duplications in which highly homologous DNA sequences (>96% identity) are present at both ends of the haplotype. Moreover, the 3-Mb DNA segment, flanked by the duplications, is inverted in the mouse genome when compared with the orientation in human and chimp. The segmental duplication architecture surrounding the MS locus raises the possibility that a nonallelic homologous recombination between duplications could affect the biological activity of the regional genes, perhaps even contributing to the genetic background of MS.